Invisible Crimes
XII, 251 p.
Keywords: Invisible Crimes is an edited volume containing a collection of articles from a distinguished panel of academics. The book explores many features of 'invisible' crimes and in doing so provides numerous examples of hidden crimes and victimisations. The book will be invaluable to students of criminology at both undergraduate and postgraduate level. It will also inspire academics from a range of disciplines to update, rewrite and offer new courses on neglected crimes and victimisations.